The Relationship between Knowledge and Attitudes with Measures to Prevent the Spread of Covid – 19 in the Community at Pasar Pendidikan, Medan Perjuangan District in 2020 - Aulia Amri Parunduri; Donal Nababan; Mido Ester J. Sitorus (TOUR HEALTH JOURNAL, 2023)
Purpose: Corona Virus or COVID-19 is a large family of viruses that can cause pain or death in humans, the virus was first reported in December 2019 in wuhan city, China and spread to other countries starting in January 2020. The purpose of this research is to analyze the relationship of knowledge and attitude with the prevention of the spread of covid 19 in krakatau market area medan by 2020. This type of research is analytical research to find out the relationship of knowledge and attitude with prevention of the spread of covid-19 in the Community at Pasar Pendidikan, Medan Perjuangan District in 2020. Method: This research was conducted in the working area of krakatu market. The study was conducted during August 2020. The population of this study is the sales in the Community at Pasar Pendidikan, Medan Perjuangan District in 2020 as many as 90 respondents. Research samples are conducted with a total sampling technique that is the entire population used as a research sample. Processing using editing, coding and tabulating and data analysis of univariate and bivariate using Chi-square test. Results: The results of the study have a link between knowledge and covid-19 prevention measures in the community at the Pasar Pendidikan in Medan Perjuangan sub-district in 2020 with a value of p =0.000< 0,05. There is a relationship between attitudes and covid-19 prevention measures in the community at Pasar Pendidikan in Sub-District, Medan Perjuangan District in 2020 with a value of p = 0.002 < 0,05. Disscusion and Conclusion: Advice for sales needs to be aware of sales to adhere to health protocols in the time of the COVID-19 pandemic with behavior changes namely using masks, physical distancings and healthy and clean living behaviors. In addition, the importance of the role of socialization and monitoring health officers in the community in the prevention of COVID-19. For tax officials, it is best for officers to pay more attention to sales people, especially reminding officers to follow health protocols to avoid covid-19